The Substance of Cold: Indonesians’ Use of Cold Weather Theory to Explain Everyday Illnesses - Anggoro, Florencia K.; Jee, Benjamin D. (Frontiers in Psychology, 2021)
Many people across the world use cold conditions to explain illness. In Indonesia, the concept masuk angin, or “trapped wind,” appears to reflect this line of folknatural thinking. Interestingly, Indonesians distinguish masuk angin from the common cold, which is a frequent target for “cold weather” explanations in other cultures (Baer et al., 1999; Sigelman, 2012). We interviewed Indonesian 3rd- and 5th-grade children, lay adults, and medical expert adults, about the cause, contagiousness, and treatment of everyday illnesses: the common cold, the flu, and masuk angin. Most Indonesian children, and especially adults, believed that cold and flu are caused by germs and are contagious. In contrast, most children and lay adults (but not experts) attributed masuk angin to cold conditions and viewed it as non-contagious. These findings reveal how folknatural and scientific theories of illness coexist in the minds of Indonesian children and lay adults.